2018
DOI: 10.1155/2018/7415975
|View full text |Cite
|
Sign up to set email alerts
|

Time‐, Sex‐, and Dose‐Dependent Alterations of the Gut Microbiota by Consumption of Dietary Daikenchuto (TU‐100)

Abstract: Medications or dietary components can affect both the host and the host's gut microbiota. Changes in the microbiota may influence medication efficacy and interactions. Daikenchuto (TU-100), a herbal medication, comprised of ginger, ginseng, and Japanese pepper, is widely used in Japanese traditional Kampo medicine for intestinal motility and postoperative paralytic ileus. We previously showed in mice that consumption of TU-100 for 4 weeks changed the gut microbiota and increased bioavailability of bacterial gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Finally, gut dysbiosis has been proposed as an important contributing factor to the increasing prevalence of UC, with a potential role for the related clinical-therapeutic phases [32,62,63]. Consistently, we found a signi cant ability of the genus Bilophila and Fusobacterium to selectively associate with cases of UC activity/remission.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, gut dysbiosis has been proposed as an important contributing factor to the increasing prevalence of UC, with a potential role for the related clinical-therapeutic phases [32,62,63]. Consistently, we found a signi cant ability of the genus Bilophila and Fusobacterium to selectively associate with cases of UC activity/remission.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, AF12 sp. has been observed to increase in relative abundance after dietary supplementation of the herbal remedies daikenchuto and the Lingzhi mushroom (G. lucidum) [104,105]. In particular, in Meneses et al, the increase in the relative abundance of AF12 after Lingzhi mushroom consumption by C57BL/6 mice was followed by lowered cholesterol and greater excretion of fecal bile acids [105].…”
Section: Discussionmentioning
confidence: 95%
“…Various other herbal medicines have also been reported to affect the composition of intestinal microbiota. For example, daikenchuto, which is used to treat adhesive bowel obstruction and "a feeling of coldness in the abdomen, " prevented a loss of microbiome diversity in a rat model of fasting stress (Yoshikawa et al, 2013) in a manner that depended on treatment duration, sex, and treatment dose (Miyoshi et al, 2018). Sennoside, which is present in daisaikoto, is metabolized by the gut microbiota to Rheinanthrone, which promotes peristalsis (Matsumoto et al, 2012), a major driver of microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the alteration in the gut microbiome (dysbiosis) caused by the onset of obesity improves after a prolonged period of dieting, but it has also been confirmed that weight regain easily occurs within approximately 3 months of the dieting period in advanced examination. It has also been reported that the duration of changes in the gut microbiome after discontinuation of the administration of Chinese medicine varies according to its dose and duration (Miyoshi et al, 2018). As Chinese medicine often improves its targeted condition within 2-3 months when there are no side effects, we used a dieting period of 3 months.…”
Section: Dieting Processmentioning
confidence: 99%